Chapter Il Mediterraneo, tra unità, frammentazione e oblio - Bicchi, Federica (Studi e saggi, 2022)
In academic and/or cultural debate, the word «Mediterranean» elicits mixed reactions and is revealing of normative considerations and the role of politics. This chapter explores two different perspectives that emerge from the extensive literature on this subject, and suggests a third, inspired by the contemporary trend of the debate (or rather, its absence). First, the chapter examines conceptions of the Mediterranean as a unitary entity or political actor in and of itself. The Mediterranean as a «cradle of civilization», originally described by Braudel, has been taken up more recently by Horden and Purcell, who emphasized the central role of connectivity between local communities, and by the Italian school of geo-philosophy headed by Bassano, for whom the Mediterranean is a specific value system to be respected. A second perspective emphasizes instead the Mediterranean as an area of conflict, characterized by deep fault lines. Huntington's position, captured by the expression «clash of civilizations», has been taken up and reworked by the post-colonial perspective, which sees the Mediterranean as an area characterized by permanent tensions. The chapter suggests a third option, however, noting that the word «Mediterranean» is disappearing from political vocabularies.